In vitro fungitoxic activity of Larrea divaricata cav. extracts - Quiroga, Emma Nelly (2004)
Aims: To evaluate the fungitoxic activity of Larrea divaricata Cav. extract and one of its components against yeasts and fungi. This activity was compared with the action of ketoconazole, a known synthetic antimycotic.To evaluate the fungitoxic activity of Larrea divaricata Cav. extract and one of its components against yeasts and fungi. This activity was compared with the action of ketoconazole, a known synthetic antimycotic. Methods and Results: Antifungal activity of Larrea divaricata extract and of a fraction (Fr. B) purified by thin layer chromatography, was investigated using different methodologies. Both exhibited strong activity against the majority of the assayed fungi. Only Fusarium oxysporum and Schizophyllum commune growth was not affected with the assayed conditions. The fungitoxic and cytotoxic activity of the ethanolic extract and ketoconazole were compared.Antifungal activity of Larrea divaricata extract and of a fraction (Fr. B) purified by thin layer chromatography, was investigated using different methodologies. Both exhibited strong activity against the majority of the assayed fungi. Only Fusarium oxysporum and Schizophyllum commune growth was not affected with the assayed conditions. The fungitoxic and cytotoxic activity of the ethanolic extract and ketoconazole were compared. Conclusions: Ethanolic extracts of L. divaricata Cav. produce growth inhibition of several fungi. One of its constituents with the same activity was purified and identified as a glycoside of a flavanone. A comparison with the action of ketoconazole, which is currently used as antimycotic and can cause adverse health effects was made.Ethanolic extracts of L. divaricata Cav. produce growth inhibition of several fungi. One of its constituents with the same activity was purified and identified as a glycoside of a flavanone. A comparison with the action of ketoconazole, which is currently used as antimycotic and can cause adverse health effects was made. Significance and Impact of the Study: Our data suggest that L. divaricata extract contains, at least, one compound of phenolic nature, with fungitoxic potency against yeasts and fungi.Our data suggest that L. divaricata extract contains, at least, one compound of phenolic nature, with fungitoxic potency against yeasts and fungi.